ANALISIS PEMAHAMAN PEMBELAJARAN IPS PADA SISWA KELAS VI DI SD NEGERI 2 TANJUNG AGUNG TIMUR - Reni Sasmita; Liza Murnivianti; Novianti Novianti (Universitas Negeri Medan, 2022)
Abstract : Analysis of Social Science Learning Understanding in Class VI Students at SD Negeri 2 Tanjung Agung Timur. The purpose of this study was to determine the level of understanding of social studies learning in class VI students at SD Negeri 2 Tanjung Agung Timur. The object of this research is students' understanding of the history of ASEAN social studies subjects for class VI SD Negeri 2 Tanjung Agung Timur. The informants in this study are research subjects, which means people who provide information about the situation and condition of the research setting. The research method used in this study is a qualitative descriptive method. The data collection techniques in this study used tests, interviews and documentation, while the data collection techniques (data collection), data analysis (data reduction), data presentation (data display), and conclusion drawing (cluster drawing). Based on the results of the study, it was found that the level of understanding of social studies understanding was an average value of 74 which was in the sufficient category. The teacher's role in understanding social studies material about ASEAN in Grade VI students of SD Negeri 2 Tanjung Agung Timur is that the teacher explains the historical activities of ASEAN in accordance with the guidelines for using good learning resources. Efforts to improve students' understanding in social studies learning, teachers must be able to master the class and become a fun teacher.Keywords: Understanding, Social Studies Abstract : Analisis Pemahaman Pembelajaran Ips Pada Siswa Kelas VI Di SD Negeri 2 Tanjung Agung Timur. Tujuan Penelitian ini adalah untuk mengetahui Tingkat Pemahaman Pembelajaran IPS Pada Siswa Kelas VI di SD Negeri 2 Tanjung Agung Timur. Adapun Objek dalam penelitian ini adalah pemahaman siswa pada materi sejarah ASEAN mata pelajaran IPS Kelas VI SD Negeri 2 Tanjung Agung Timur. Adapun informan dalam penelitian ini adalah subjek penelitian, yang berarti orang yang memberikan informasi tentang situasi dan kondisi latar penelitian. Metode penelitian yang menggunakan dalam penelitian ini adalah metode deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini menggunakan tes, wawancara dan dokumentasi, sedangkan teknik pengumpulan data (data collection), analisis data (data reduction), penyajian data (data display), dan penarikan kesimpulan (cunclusin drawing). Bedasarkan hasil penelitian didapatkan bahwa tingkat pemahaman pemahaman IPS sebesar dengan nilai rata-rata 74 yang termaksud dalam kategori cukup. Peranan guru terhadap pemahaman IPS materi sejarah ASEAN pada Siswa Kelas VI SD Negeri 2 Tanjung Agung Timur adalah guru menjelaskan materi kegiatan sejarah ASEAN sesuai dengan panduan menggunakan sumber belajar yang baik. Upaya untuk meningkatkan pemahaman peserta didik dalam pembelajaran IPS guru harus dapat menguasai kelas dan menjadi guru yang menyenangkan. Kata Kunci : Pemahaman, IPS